Changes in Autonomic Nervous System Indices Assessed by Heart Rate Variability After Mugwort Moxibustion - Jin Suk Koo (Journal of Korean Medicine, 2026)
Objectives: This study aimed to investigate changes in autonomic nervous system–related indices assessed by heart rate variability (HRV) following mugwort (Artemisia vulgaris) moxibustion.Methods: This quasi-randomized controlled trial enrolled 44 adult outpatients who visited a Korean medicine clinic in Andong, Republic of Korea, with non-specific health complaints such as stress, fatigue, or sleep disturbance. Participants were systematically assigned to either the moxibustion group or the control group based on their visiting days. In the moxibustion group, mugwort moxibustion was applied to the Shenque (CV8) point for 30 minutes under standardized conditions. Heart rate variability (HRV) was measured before and after the intervention, and HRV-based autonomic nervous system parameters were analyzed to evaluate physiological changes associated with the treatment.Results: After moxibustion treatment, stress resistance, autonomic nervous system activity, SDNN, and TP significantly increased, while the stress index and mean heart rate significantly decreased (p < 0.05). These changes were accompanied by increases in heart rate variability parameters associated with parasympathetic function.Conclusions: These findings suggest that mugwort moxibustion may be associated with favorable changes in heart rate variability–related parameters reflecting autonomic nervous system function.